Peran Budaya Lokal dalam Hubungan antara Kepemimpinan Inklusif dan Kinerja Karyawan Generasi Z di PT Bank Sulteng - Aksa, Abail; Harnida Wahyuni Adda; Yoberth Kornelius; Muh. Riswandi Palawa (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the effect of inclusive leadership on Generation Z employee performance at PT Bank Sulteng and examine the moderating role of Kaili local culture. A quantitative approach was employed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) on 39 Gen Z respondents. The results show that inclusive leadership does not significantly affect employee performance, and local cultural internalization does not moderate the relationship. These findings suggest that local cultural values are not yet operationally embedded in organizational work systems. The study implies the importance of contextual inclusive leadership practices and local cultural integration to enhance Gen Z performance in regional banking. Keywords: inclusive leadership, local culture, Kaili values, employee performance, Generation Z, organizational behavior, internalization, banking sector